Answer:
x2-5x-8=0
Step-by-step explanation:
Two solutions were found :
x =(5-√57)/2=-1.275
x =(5+√57)/2= 6.275
Reformatting the input :
Changes made to your input should not affect the solution:
(1): "x2" was replaced by "x^2".
Step by step solution :
Step 1 :
Trying to factor by splitting the middle term
1.1 Factoring x2-5x-8
The first term is, x2 its coefficient is 1 .
The middle term is, -5x its coefficient is -5 .
The last term, "the constant", is -8
Step-1 : Multiply the coefficient of the first term by the constant 1 • -8 = -8
Step-2 : Find two factors of -8 whose sum equals the coefficient of the middle term, which is -5 .
-8 + 1 = -7
-4+ 2 = -2
-2+ 4 = 2
-1 + 8 = 7
(x+1) (x+3)
the zeroes of the function are negative 1 and negative 3
Answer:
<em>Parallel</em>
Step-by-step explanation:
The dotted lines are parallel because they have the same <u>gradient</u> to each other, this means the two dotted lines will <u>never</u> touch each other.
Have a great day <3
Answer:
357
Step-by-step explanation:
A) We replace x = - 5 and u = 3 into -3x^3 -2y^2
and we have -3x^3 -2y^2= -3*(-5)^3 -2*3^2= -3*(-125)- 2*9
or -3x^3 -2y^2 = 375-18= 357
The answer is 357.
B) Replace h = -2 into h^2-3h+2
we have h^2-3h+2 = (-2)^2 -3*(-2) +2 = 4 +6 + 2= 12
The answer is 12
Have a good day.
Answer:
113.04
Step-by-step explanation:
the equation for the area of a circle is pie times radius squared